Religious Extremism and Poverty Keys to the Spread of Insurgency in Lake Chad Basin. - Umeh, Lucy Chinwe; Mbaeze, Netchy; Ugwuozor, Samuel (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
This study investigated Religious extremism and Poverty as keys to the spread of Insurgency in the Lake Chad Basin. Regional Security complex Theory propounded by Barry Buzan and Ole Waever, ex-post facto research design, documentary method of data collection and descriptive qualitative method of data analysis were employed in the analysis. This study found that the grievance of religious intolerance and high rate of poverty within the Chad basin paved way for easy spread of insurgency in the region, and that the Islamic State of West Africa Province (ISWAP) insurgency has eroded the foundation of the Lake Chad Basin’s security governance leading to the socioeconomic decline. The researcher therefore recommends that Governments within the Chad Basin should direct a large portion of their resources toward human capital development, capacity building and elimination of socioeconomic challenges in order to wall off poverty and religious extremism.